The importance of university, students and students' union partnerships in student-led projects: A case study. Issue 8 (25th September 2019) - Briggs, Sarah Jayne; Robinson, Zoe P.; Hadley, Rachel Louise; Laycock Pedersen, Rebecca
Abstract : Purpose: This paper aims to explore a single-institution case study of partnership working between students, the University and Students' Union, through four student-led sustainability projects. The paper analyses the role and value of these partnerships and provides advice for other institutions on effective partnership working between these stakeholders. Design/methodology/approach: A single case study of partnership working with multiple embedded units of analysis (four projects) is presented based on reflections of practitioners involved in the projects who have different roles within the University and Students' Union. Findings: The longevity and effectiveness of student-led projects, and disciplinary-breadth of students engaged, can be enhanced by greater collaboration with, and integration into, University and Students' Union systems. Partnership working between different stakeholders is key to overcoming challenges and the success of student-led projects, helped by key staff "enablers". These projects provide myriad learning opportunities for developing change agency skills, even where projects are relatively short-lived and could be seen as failures in terms of longevity. Research limitations/implications: This analysis is based solely on practitioner reflections, with limited direct quantification or qualitative data on the projects' impacts on the students themselves. Originality/value: This paper draws together the experiences and reflections of four practitioners with different roles within the University and Students' Union across four different projects and provides advice to generate student-led sustainability projects which have longevity and impact for wider student populations and future generations of cohorts.